2017
DOI: 10.1590/1678-4685-gmb-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between XPD, RAD51, and APEX1 DNA repair genotypes and prostate cancer risk in the male population of Rio de Janeiro, Brazil

Abstract: Susceptibility to cancer ensues in individuals carrying malfunctioning DNA repair mechanisms. The impact of Single Nucleotide Polymorphisms (SNPs) in key DNA repair mechanisms on risk for prostate cancer was investigated in this case-control study. Samples consisted of 110 patients with confirmed prostate cancer and 200 unaffected men, from Rio de Janeiro, Brazil. XPD/Lys751Gln (rs13181), APEX1/Asp148Glu (rs1130409), and RAD51/G135C (rs1801320) SNPs were analyzed by PCR-RFLP. Allelic and genotypic frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Titles and abstracts were screened for all papers produced by the literature search. Studies excluded from the primary analyses during title and abstract screening were reviews, [24][25][26] editorials, 27 animal or in vitro studies, 28 mechanistic studies (even if they used endpoints potentially related to clinical cancer, as epigenetic markers, telomere length, endocrine response), [29][30][31][32] papers on study protocols, 33 biostatistics methods papers, 34,35 epidemiological profiles and cohort descriptions, 36,37 risk/ exposure assessments 38 and other studies where human cancer was not a primary outcome. 39 The following search terms were used in PubMed to identify relevant journal articles assessing the relationship between human exposure to pesticides and cancer, which were published in 2017 or later:…”
Section: Methodsmentioning
confidence: 99%
“…Titles and abstracts were screened for all papers produced by the literature search. Studies excluded from the primary analyses during title and abstract screening were reviews, [24][25][26] editorials, 27 animal or in vitro studies, 28 mechanistic studies (even if they used endpoints potentially related to clinical cancer, as epigenetic markers, telomere length, endocrine response), [29][30][31][32] papers on study protocols, 33 biostatistics methods papers, 34,35 epidemiological profiles and cohort descriptions, 36,37 risk/ exposure assessments 38 and other studies where human cancer was not a primary outcome. 39 The following search terms were used in PubMed to identify relevant journal articles assessing the relationship between human exposure to pesticides and cancer, which were published in 2017 or later:…”
Section: Methodsmentioning
confidence: 99%
“…According to Ana et al 35 the APE1 deficiency reduced the risk of developing prostate cancer, and this finding is explained by the simultaneous reduction of important DNA repair pathways. As a result, prostatic tissue is likely protected from the spread of potentially cancerous clones and prostatic cells have probably died.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, numerous studies have identified polymorphisms located in genes of DSBR associated to the risk of a variety of benign and malignant tumors, for example, XRCC1 R399Q in breast cancer, 18 RAD51 135G/C in colorectal cancer, 19 XPD Lys751Gln in prostate cancer and so on. 20 The present study focuses on the effect of 3ʹ-UTR polymorphisms of DSBR genes on PTC risk based on a medium-sized case–control study.…”
Section: Discussionmentioning
confidence: 99%